Gerakan Bersih-bersih Pantai Balekambang dari Sampah Plastik - Nazriati Nazriati; Yudhi Utomo; Fauziatul Fajaroh; Suharti Suharti; Danar Danar; Endang Ciptawati (University of Merdeka Malang, 2020)
The beach is an attractive place to unwind from your daily routine. The beauty of the beach must always be maintained so that comfort can still be obtained for everyone who visits it. The beach becomes a comfortable place if cleanliness is maintained. Plastic waste, if any along the coast, can be carried by the waves into the ocean. Plastic waste brought to sea can be consumed by marine biota because marine biota cannot distinguish between plastic and food waste. This community service activity intends to inspire visitors (tourists), managers and traders at Balekambang beach to care about the environment. A well-preserved environment will be a legacy that will be left on the next generation. The survey results show that visitors understand the meaning of waste and are willing to dispose of waste in its place. DOI: https://doi.org/10.26905/abdimas.v5i2.3573